In silico study identifies hub genes and regulatory network associated with the pathogenesis of Japanese encephalitis virus - Arvind Kumar; Gyanendra Bahadur Chand; Gajendra Kumar Azad (Egyptian Journal of Medical Human Genetics)
Abstract Background Japanese encephalitis (JE) is a mosquito-borne viral disease caused by Japanese encephalitis virus (JEV). Approximately 3 billion people from South-East Asia are at risk of this disease; however, no definitive cure for JE has been developed. Therefore, it is important to understand the biology of JE by identifying critical genes and miRNAs involved in the pathogenesis. Therefore, this study was undertaken to identify hub genes and regulatory network associated with JE pathogenesis using several computational tools such as GEO2R, GeneMania, Cytohubba, WebGestalt, miRTarBase and mathematical modelling. Results Our data revealed VEGFA and WNT5A genes are major contributing factors for the development of primary stage of invasive JEV. These two genes were found to be regulated by transcription factor and miRNA targets from multiple databases. The analysis revealed that the activation of VEGFA and WNT5A are mediated by several transcription factors (TFs) that include EGR1, EPAS1, ETS1, FOS, HIF1A and GLI3, GLI2, GLI1, respectively. Furthermore, we also identified hsa-miR-205 and hsa-miR-330-5p miRNAs that regulates the repression of VEGFA and WNT5A. The mathematical modelling supports the role of these two miRNAs in the initiation of the regulatory pathogenesis in JEV. Additionally, we have shown that the type 1 and type 2 coherent and incoherent feed forward loops help to determine the VEGFA gene regulation by TFs and miRNAs. Conclusions This study provides potential new insights into the molecular mechanisms connecting JEV with VEGFA/WNT5A via miRNAs. Altogether, studies on JE pathogenesis will help to identify drug targets and also develop new strategies for JE treatment.